An international multi-institutional analysis of operative morbidity in patients undergoing elective diverticulitis surgery - Altinel,Yuksel (2022)
SUMMARY OBJECTIVE: We investigated surgical complications of elective surgery for diverticulitis in international multi-institution to identify a prediction model for potential opportunities of quality improvement. METHODS: We identified 1225 patients who underwent elective surgery for diverticulitis between January 2010 and January 2018. The data were obtained from the National Surgical Quality Improvement Program and the Turkish Diverticulitis Study Group Collaborative, retrospectively. RESULTS: We observed that the presence of chronic obstructive pulmonary disease (OR: 3.2, 95%CI 1.8–5.9, p<0.001) or abscess at the time of surgery (OR: 1.4, 95%CI 1.2–1.7, p£0.001) is associated with a higher rate of minor complications, while comorbidities such as dyspnea (OR: 2.8, 95%CI 1.6–4.9, p£0.001) and preoperative sepsis (OR: 4.1, 95%CI 2.3–7.3, p£0.001) are associated with major complications. The centers had similar findings in minor and major complications (OR: 0.8, 95%CI 0.5–1.4, p=0.395). The major independent predictors for complications were malnutrition (low albumin) (OR: 0.5, 95%CI 0.4–0.6, p<0.001) and the American Society of Anesthesiology score (OR: 1.7, 95%CI 1.2–2.4, p=0.002). CONCLUSION: Regarding the major and minor complications of diverticulitis of elective surgery, the malnutrition and higher American Society of Anesthesiology score showed higher impact among the quality improvement initiatives.